2010
DOI: 10.1038/sc.2010.150
|View full text |Cite
|
Sign up to set email alerts
|

Is manual wheelchair satisfaction related to active lifestyle and participation in people with a spinal cord injury?

Abstract: Study design: Cross-sectional study. Objectives: To describe the satisfaction of the manual wheelchair user with hand rim wheelchairrelated aspects (for example, dimensions, weight and comfort) and wheelchair service-related aspects and to determine the relationship between wheelchair users' satisfaction, personal and lesion characteristics, and active lifestyle and participation in persons with a spinal cord injury (SCI). Setting: Eight Dutch rehabilitation centers with a specialized SCI unit. Methods: The Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 16 publications
5
28
2
1
Order By: Relevance
“…de Groot et al showed a relationship between participation and simplicity of use and between an active lifestyle and MW dimensions [10]. They showed that some aspects of the MW should be optimized because they are related to an active lifestyle and participation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…de Groot et al showed a relationship between participation and simplicity of use and between an active lifestyle and MW dimensions [10]. They showed that some aspects of the MW should be optimized because they are related to an active lifestyle and participation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that level of satisfaction with the wheelchair and overall quality of life of persons with spinal cord injury (SCI) were positively related in China and the Netherlands [12]. de Groot et al highlighted key aspects of the wheelchair (i.e., dimensions and simplicity of use) that are important for optimizing an active lifestyle and social participation [10]. The importance of good wheelchair adjustments has been previously described in wheelchair ergonomics literature [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a number of studies have used these assessments to gauge user satisfaction with wheelchairs. 11,17,18 These assessments were not used in this study because they are very extensive and time consuming to administer and not appropriate if trying to get a broad impression of user satisfaction across a wide range of equipment as done in this study.…”
Section: Discussionmentioning
confidence: 99%